Effectiveness of Detailed Information on Subconscious Motor Sequence Learning in Acute Stroke - Asthana, Sumit; Rizvi, Arif; Rasheed, Rutba (Journal of Biomedical and Pharmaceutical Research, 2024)
Introduction: Stroke is defined as a rapidly developing clinical sign of focal disturbance of central function of presumed vascular origin & of more than 24-hours duration1. Clinically a variety of deficits are possible including changes in the level of consciousness & impairment of sensory, motor, cognitive , perceptual & language functions2. Although it is unequivocal that the extremities contra lateral to the unilateral cerebral lesion are more affected than the ipsilesional extremities, there is now a large body of research that suggests that the ipsilesional extremities are not normal often clinically assumed as “the non affected side” ,particular to the upper extremity there is increasing evidence of sensory-motor control deficits on the ipsilesional side3. These ipsilesional deficits may reflect motor control deficits that are masked on the contralateral side by hemiplegia and hemisensory loss3. The non-dominant hemisphere plays a primary role in the function of complex visuo-spatial accuracy, whereas the dominant hemisphere is mainly involved in the motor control of bilateral upper limbs as well as the performance of complex tasks. Although the cause of ipsilesional movement abnormalties have not been elucidated accurately, several possible mechanisms have been suggested i.e. the injury of the uncrossed corticospinal system, inhibitory transcallosal influence on the unaffected hemisphere, the different roles of side-to-side hemispheric function depending on the specific properties of the task & bilateral hemispheric processing for high cognitive activity4. In persons with stroke, deficits in targeted movements, compared with comparison groups, have been identified in the ipsilateral extremities, even when clinical measures of the upper extremities reveal little or no deficit5 Objective: To study effectiveness of detailed information on subconscious motor sequence learning in acute stroke Research Design: Observational design Methodology: A total of 22 subjects with anterior circulation stroke (diagnosed by neurologist) were included in the study. In the group A (No-Explicit Information group) 13 subjects were recruited (total 15 subjects were recruited, but 2 patients left in between). In the group B (Explicit Information Group) 9 subjects were recruited. Result: Descriptive statistics is used to analyze subject characteristics. 22 subjects recruited for the study were randomly assigned to each group, group A (Non EI) with 9 males and 4 females with mean age of 59.94 years and mean score on MMSE, & COVS, were 27.92 and 6.00. Group B (EI) with 8 males and 1 female with mean age of 58.22 years and mean score on MMSE, & COVS were 29.00 and 6.56.On comparing the Age (p=0.75), MMSE score (p=0.09), and COVS score (p=0.08) between the two groups, the results were not significant (at p<0.05). Thus both the groups are comparable. Conclusion: Our findings suggest that explicit information when given prior to physical practice improved implicit motor sequence learning in subjects with acute stroke; however subjects were not able to express it explicitly. Keywords: non-dominant hemisphere, Stroke, disability, uncrossed corticospinal, explicit and implicit learning